Combined effects of gibberellin and vermiwash on the life history and antioxidant system of Phthorimaea absoluta (Meyrick) in tomato plants - Azim Nemati; Jalal Jalali Sendi; Yaghoub Fathipour (Scientific Reports)
Abstract Tomato (Lycopersicon esculentum Miller), is a globally important agricultural product, yet it is under significant threat from pests such as the tomato leaf miner, Phthorimaea absoluta (Meyrick) (Lepidoptera: Gelechiidae). This study investigates the combined effects of gibberellin and vermiwash treatment on the life history and antioxidant system of P. absoluta. Given the pest’s resistance to many chemical pesticides, alternative control methods are crucial. Gibberellins are plant growth hormones known for their role in plant development and stress responses, while vermiwash is a bio-fertilizer rich in nutrients and microbial agents. We applied gibberellin and vermiwash (GV treatment) to tomato plants and assessed the impact on P. absoluta developmental stages, reproduction, and enzymatic activities. Our results show significant differences in larval development times (32.06 ± 0.39) and survival rates (0.53 ± 0.09) between treated and control groups (27.38 ± 0.35 and 0.80 ± 0.07, respectively). The GV treatment prolonged the total lifespan of P. absoluta (44.31 ± 0.51) but reduced its intrinsic rate of increase (r) (0.086 ± 0.009) and finite rate of increase (λ) (1.090 ± 0.009). Enzymatic assays revealed altered antioxidant and detoxifying enzyme activities in treated larvae. This study suggests that gibberellin and vermiwash treatments could be incorporated into pest management strategies for sustainable tomato production.